2009
DOI: 10.1371/journal.pone.0005896
|View full text |Cite
|
Sign up to set email alerts
|

SLC30A3 (ZnT3) Oligomerization by Dityrosine Bonds Regulates Its Subcellular Localization and Metal Transport Capacity

Abstract: Non-covalent and covalent homo-oligomerization of membrane proteins regulates their subcellular localization and function. Here, we described a novel oligomerization mechanism affecting solute carrier family 30 member 3/zinc transporter 3 (SLC30A3/ZnT3). Oligomerization was mediated by intermolecular covalent dityrosine bonds. Using mutagenized ZnT3 expressed in PC12 cells, we identified two critical tyrosine residues necessary for dityrosine-mediated ZnT3 oligomerization. ZnT3 carrying the Y372F mutation prev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
62
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 51 publications
(68 citation statements)
references
References 56 publications
6
62
0
Order By: Relevance
“…Recently, co-immunoprecipitation and Western blot analysis revealed that ZnT3 forms covalent homodimers mediated by intermolecular dityrosine bonds, which are induced by oxidative stress (22); these covalent dityrosine bonds were found to modulate subcellular localization and zinc transport activity of ZnT3 (22). Herein we showed that homodimers of ZnT3 localize at intracellular vesicles, consistent with its vesicular localization in the brain (45).…”
Section: Discussionsupporting
confidence: 69%
See 2 more Smart Citations
“…Recently, co-immunoprecipitation and Western blot analysis revealed that ZnT3 forms covalent homodimers mediated by intermolecular dityrosine bonds, which are induced by oxidative stress (22); these covalent dityrosine bonds were found to modulate subcellular localization and zinc transport activity of ZnT3 (22). Herein we showed that homodimers of ZnT3 localize at intracellular vesicles, consistent with its vesicular localization in the brain (45).…”
Section: Discussionsupporting
confidence: 69%
“…(b) Consistently, this C-terminal region of ZnT5 is important for recognizing ZnT6 as a partner for heterodimerization (23). (c) The corresponding region of ZnT3 appears to regulate intracellular trafficking and zinc transport activity by forming a covalent dityrosine bond in response to oxidative stress (22). (d) The C-terminal region was further found to be important for proteinprotein interactions between ZnT1 and the protein kinase Raf-1 (44).…”
Section: Discussionmentioning
confidence: 82%
See 1 more Smart Citation
“…This enabled us to perform detailed analysis of the functions of ZnTs in the supply of zinc to zinc-requiring enzymes such as TNAP. Our findings revealed that over 95% of TNAP protein is activated by ZnT5/ZnT6 heterodimers and ZnT7 homo-oligomers and that the other ZnTs barely contribute, despite having zinc transport activity in the secretory pathway when exogenously expressed (25,36,37). Treatment with zinc pyrithione increased the zinc content in the early secretory pathway and, consistently, increased TNAP activity via other minor pathways, but this effect was not comparable in magnitude with that of ZnT5/ZnT6 heterodimers and/or ZnT7 homo-oligomers.…”
Section: Discussionmentioning
confidence: 75%
“…ZnT transporters are predicted to have six TM helices with the exception that ZnT5 has a long NH 2 -terminal portion with nine putative TM helices. ZnT transporters form homodimers (114,180,230,231,291,353,391), again with the exception that ZnT5 forms heterodimers with ZnT6 (114,195,230). The cytosolic COOH-terminal portion, which is important for their dimerization (114,353), contributes to other proteinprotein interactions and enables ZnT transporters to control the activity of counterpart proteins or to be controlled by counterpart proteins (114,186,189,355).…”
Section: Role Of Zinc Transporters In Zinc Homeostasis and Metabolismmentioning
confidence: 99%